The Impact of Challenge Stressors and Hindrance Stressors on Recovery Experiences and Job Performance - Messallam, Aly; Attia, Ghada; El-Dokani, Hadeer (The Arab Journal of Administration, 2018)
This study investigated the impact of challenge stressors and hindrance stressors on recovery experiences and job performance, as well as tested the mediating role of recovery experiences in those relationships. Data were collected from 251 Egyptian nurses working in Alexandria University Hospitals. The theoretical model was tested by using Structural Equation Modeling (SEM). Specifically, the current study examined the positive relationship between challenge stressors and both recovery experiences and job performance. In addition, the current study investigated the negative relationship between hindrance stressors and both recovery experiences and job performance. Finally, the study examined the positive effect of recovery experiences on job performance Results indicated that challenge stressors were negatively related to both psychological detachment and relaxation. SEM also revealed that psychological detachment was positively related to in-role behaviors. However, the current study didn’t support the mediating role of recovery experiences in the hypothesized relationships. Also, the results didn’t support the negative relationships between hindrance stressors and recovery experiences and job performance. Thoughts for future research were provided.